Pencegahan Kenakalan dan Kejahatan Remaja di Polda Bali - Lubis, Rahmadsyah (Prisani Cendekia, 2024)
Juvenile delinquency is a major problem of order and security in the Bali Regional Police as a tourist visiting area. Vandalism, student brawls, drug use and pornography are a number of criminal acts that exist. Basically, teenagers in Bali are not aware of the delinquency and crime that exists. Most of them think all this is normal. Therefore, counseling and socialization about delinquency and crime among teenagers and children at the Bali Regional Police is very important. This activity provides real information about legal regulations regarding delinquency and crime among teenagers. An important finding is the need for strong control over the actions of teenagers and children by various parties, especially parents, schools and villages in the areas where they live. Supervision over the use of gadgets from existing social media must be carried out strictly and filtered well because many people engage in persuasion and incitement.